Aerodynamic Noise Control of the Converter for Railway Vehicle - YAN Meng; HE Caichun; GUO Fulin; YANG Tao (Kongzhi Yu Xinxi Jishu)
In order to reduce the noise of converters used in rail vehicles, one type converter was taken as a research object. By analyzing noise test results in actual running state, it not only identified fan aerodynamic noise as its main noise source, but also found that noise spectrum peak mainly concentrated in the range of 500 ~ 4 000 Hz and big noise mainly concentrated in the outlet. An optimized acoustic structure was designed by using absorption material on the inner of the air duct and the structure for ducting of the outlet. Simulation and experimental results show that the noise of the converter with this optimized design is decreased obviously, and aerodynamic noise can be controlled effectively and total noise value is reduced.